2015
DOI: 10.1007/s10916-015-0376-2
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Agents Applied in Healthcare

Abstract: Intelligent agents and healthcare have been intimately linked in the last years. The intrinsic complexity and diversity of care can be tackled with the flexibility, dynamics and reliability of multi-agent systems. The purpose of this review is to show the feasibility of applying intelligent agents in the healthcare domain and use the findings to provide a discussion of current trends and devise future research directions. A review of the most recent literature (2009-2014) of applications of agents in healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 118 publications
0
46
0
Order By: Relevance
“…Table 2 presents the remaning 16 reviews which present multiple types of applications and the classification of the applications of simulation studies, within those articles [7,8,12,14,16,18,20,22,25,27,28,33,34,36,37,39]. The numbers of simulation studies relating to the different application groups were identified and extracted from the sixteen reviews.…”
Section: Data Extraction 331 Types Of Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 presents the remaning 16 reviews which present multiple types of applications and the classification of the applications of simulation studies, within those articles [7,8,12,14,16,18,20,22,25,27,28,33,34,36,37,39]. The numbers of simulation studies relating to the different application groups were identified and extracted from the sixteen reviews.…”
Section: Data Extraction 331 Types Of Applicationsmentioning
confidence: 99%
“…No. of studies identified [7] (n= 93) [8] (n= 182) [12] (n= 463) [14] (n= 168) [16,18] (n= 201) [20] (n= 75) [22] (n= 70) [25] (n= 98) [27] (n= 142) [28] (n= 74) [33] (n= 117) [34] (n= 6) [36] (n= 97) [37] (n= 106) [39] (n= 232) …”
Section: Data Extraction 331 Types Of Applicationsmentioning
confidence: 99%
“…The analysis of how the Software Engineering (SE) area as well as the Requirements Engineering is evolving has been the topic of some studies (Dermeval et al, 2015), (Oliveira et al, 2011), (Laski et al, 2014), (Juziuk, Weyns and Holvoet, 2014) and (Isern and Moreno, 2016).…”
Section: Threats To Validitymentioning
confidence: 99%
“…The purpose of the review presented in (Isern and Moreno, 2016) is to show the feasibility of applying intelligent agents in the healthcare domain and use the findings to provide a discussion of current trends and devise future research directions. The authors present a review of the most recent literature (2009-2014) of applications of agents in healthcare is discussed, and two classifications considering the main goal of the health systems as well as the main actors involved have been investigated.…”
Section: Threats To Validitymentioning
confidence: 99%
“…There is no standard definition of mobile agent (some definitions can be found in literature [4,10,11,13,20]). Even so, we can obtain some common characteristics of mobile agent as summarized in [5]: mobility, autonomy, sociality, reactivity, proactivity, data acquisition, and route determination, etc.…”
Section: Introductionmentioning
confidence: 99%